Shari’ah Issues in The Operation of Retakaful and Reinsurance: A preliminary Exploration From Shari’ah Perspective - Hasan, Aznan (International Islamic University Malaysia, 2011)
This article attempts at exploring various Shari'ah issues related to the practice of takaful, retakaful, insurance and reinsurance and interaction between them in the practice of retakaful. It explores the practice of retakaful and its importance in modern takaful. The paper discusses the ruling disallowing takaful companies to cede part of their exposure to reinsurance companies on the premise of hajah and necessity. It also discusses the permissibility of allowing retakaful companies to accept ceding from conventional insurance. Various opinions, fatwa and ruling and other relevant issues have been analysed. It is found that these practices could be accepted from time to time to ensure that the practice really in compliance with this exceptional ruling